MODEL PEMBERDAYAAN MASYARAKAT DI KABUPATEN PURBALINGGA: DINAMIKA PROGRAM DAN REORIENTASI KEBIJAKAN PENGEMBANGAN - Savitri, Renny (Jurnal Desentralisasi, 2012)
The decentralization policy has long been implemented in Indonesia, but issues related to community development was still a serious problem. Hence the concept of community-based development became the most attentive development concept in the mean time. This study was conducted in 2010 in Purbalingga Regency. This study used descriptive and exploratory research method. Data collection was done by indepth interviews, discussions, field trips, and literature study. Data obtained were analyzed using qualitative research methods. Result shows that implementation of regional autonomy increased empowerment practice both in quantity and quality. Developing empowerment models are Program PNPM Mandiri Pedesaan, TMMD, PKP, Puspahastama, and Desa Sehat Mandiri. Implementation of community development programs generate positive impact on society both physical and nonphysical. Many problems encountered in community development programs, for instance in terms of policy, planning, implementation, financial, human resources, and coordination. Amongst all those problem, we expected that in the future there will be a national policy which able to integrate and synergize all government levels and units, and also stakeholders in the implementation of community development programs